P52 and Nomina Sacra - Tuckett, Christopher M. (New Testament studies, 2001)
The Rylands fragment of John (PRyl 457, usually known as P52) is widely acclaimed in the standard textbooks as the oldest surviving fragment of the text of the NT. At the time of the publication of the editio princeps, it was dated to the first half of the second century.C. H. Roberts, An Unpublished Fragment of the Fourth Gospel in the John Rylands Library (Manchester, 1935) 16. Some doubts have been cast on this in recent years and a slightly later date (second half of the second century) proposed.A. Schmidt, ‘Zwei Anmerkungen zu P. Ryl. III 457’, APF 35 (1989) 11–12. Nevertheless it is widely agreed that the fragment is one of the earliest NT manuscripts that we possess.